The Influence of Perceived Ease of Use, E-Service Quality, and Security on the Interest in Reusing the Wondr By BNI Application among Students at the Sumbawa University of Technology - Qonitha Azma Adzkia; Ryan Suarantalla (Escalate : Economics and Business Journal, 2026)
The rapid growth of digital banking applications like Wondr by BNI has transformed financial services for digital-native students at Sumbawa University of Technology, yet factors driving sustained usage remain underexplored. This study aims to analyze the influence of Perceived Ease of Use, E-Service Quality, and Security on Reuse Intention. A quantitative survey method was employed targeting an unknown population of UTS students, using purposive sampling to select 100 active Wondr by BNI users. Data were collected via structured Likert-scale questionnaires and analyzed using classical assumption tests, multiple linear regression, t-tests, F-test, and Adjusted R² through SPSS version 26. Results indicate Perceived Ease of Use significantly affects Reuse Intention (p=0.001), while E-Service Quality (p=0.075) and Security (p=0.911) show insignificant partial effects. Simultaneously, all variables jointly influence Reuse Intention (F=5.415, p=0.002), explaining 11.8% variance. In conclusion, ease of use emerges as the dominant factor, with others providing supplementary support for sustained adoption.